Revolution Elsewhere: Soviet Conformist and Non-Conformist Children’s Books of the 1960s and 1970s - Birgitte Beck Pristed (Strenae, 2018)
Soviet child education in the late 1960s toned down former early Soviet pedagogy goals to mobilize children in the present and encourage their participation in or contribution to revolution, five-year plans or war. Rather than rebel or engage in active conflict, Soviet children of ’68 were encouraged to study representations of revolutionary activism from other times in historical fiction and accounts about the 1917 Revolution and World War II, or elsewhere, be it from the third world or outer space as imagined in adventure novels. Following a short introduction to the period and a brief explanation of significant Soviet symbolic notions of the child, the article analyses the question of rebellion versus adherence in two contrasting examples of Soviet illustrated children’s books: Marta Fomina’s conformist story Independent People (Samostoiatel’nye liudi) from 1969, and Stanislav Rassadin and Benedikt Sarnov’s non-conformist In the Land of Literary Heroes (V strane literaturnykh geroev) from 1979, based on a series of radio programmes for children launched in 1970. Despite the apparent uniformity of the centrally controlled Soviet school syllabus and educational programme of the late 1960s, these two works exemplify the different and contradictory attitudes to children’s behaviour, phantasy and revolutionary potential that young readers and listeners could encounter in children’s books.